Future Generation Ultra-Fast Liquid Crystal Light Shutters - Hegde, Gurumurthy; Komitov, Lachezar; Kolev, Dimitar (Blackwell Publishing Ltd, 2012)
By proper assembling and electronic driving of two parallel single nematic liquid crystal cells with planar and vertical alignment of the liquid crystal molecules, respectively, arranged in a double cell, ultra-fast switching between bright and dark states, back and forth, is achieved.